EXPLORING STUDENT RESPONSES TO A CONSTRUCTIVELY RESPONSIVE DISCOVERY LEARNING MODEL IN DIGITAL READING - Hamidah, Ida; Hanifah, Ifah (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2025)
The shift from print to digital reading has posed new challenges for students, requiring them to navigate non-linear texts, evaluate multimodal information, and read reflectively. Although Discovery Learning has proven effective in enhancing comprehension, limited research has explored its integration with constructively responsive principles for digital reading. This study investigates student responses to a Discovery Learning model grounded in Constructive-Responsive principles at Universitas Kuningan. Using a qualitative case study design, 32 fifth-semester students from the Indonesian Language and Literature Education Program participated in four instructional sessions. Data were gathered through observation, interviews, and documentation, and then analyzed thematically. Findings show that students responded positively at each learning stage, with strong engagement during the stimulation and data collection phases. They displayed autonomy, metacognitive awareness, and strategic behavior through digital annotation, source evaluation, and collaborative synthesis. However, difficulties arose during the verification phase, particularly in assessing the credibility of sources. Overall, the model was well-received and viewed as effective in supporting digital reading comprehension. The study provides valuable insights for educators and curriculum developers seeking to promote digital literacy through responsive, student-centered instruction.